O controle do desmatamento na Amazônia : a Operação Curupira e a efetividade da proteção ambiental - Curado Filho, Diógenes Gomes (2016)
In the perspective of a healthy environment, social aspiration of man, fundamental rights, whether explicit or implicit constitutionally, they are seen from the viewpoint of rights and, above all, duties, binding both the State as the private. A very important aspect related to the environment is the forest estate, whose deforestation has compromised the full realization of one of the main fundamental human rights, the right to a healthy life in harmony with nature. A question that is made in relation to environmental protection duties, in view of the state's constitutional obligations, it's effectiveness in their work. Operation Curupira was a combat deforestation work that had its origin in the Action Plan for Prevention and Control of Deforestation in the Legal Amazon, published by the Federal Government in March, 2004. Besides to crack down on environmental offenses, in its first phase, it also had the importance of identifying the various forms that criminal organizations used to acquire through fraud, timber transportation guides, often with the support of own environmental agencies. This exemplary action command and control requires an analysis of its effectiveness as a means of combating environmental offenses, particularly illegal logging. Using as methodology, at first, an assessment of the fines imposed in the State of Mato Grosso and its subsequent storage in a period immediately after Operation Curupira, we seek to expand this comparative process through analysis of reports made annually by the Court of Union, identifying problems through the data supplied by the agencies and collecting societies in the Federal Government, including the IBAMA, which does not leave doubts concerning the effectiveness of enforcement of environmental sanctions. Aware that the effective punishment has character, individually, to prevent future recurrences, and in general terms, to prevent further damage, it can be measured if there is impunity in the case of the repression of environmental offenses, which could be endangering the fulfillment of state duties of environmental protection.